Effects of heat treatment on total phenolic contents, antioxidant and anti-inflammatory activities of Pleurotus sajor-caju extract - Saad, Wan Zuhainis; Hashim, Mahfuzatunajla; Ahmad, Syahida; Abdullah, Norhani (Taylor & Francis, 2014)
Untreated and heat treated Pleurotus sajor-caju methanolic extracts were examined for total phenolic content, antioxidant and anti-inflammatory activities. Total phenolic content was determined by using the Folin-Ciocalteu method, and results were expressed as mg gallic acid equivalent per g of sample extract. Antioxidant activity was measured by using the DPPH free radical scavenging method while anti-inflammatory activity was measured by using the Griess assay. Methanolic extracts of fresh fruiting bodies were heated at 100 and 121°C for 15 and 30 min. The results showed that total phenolic contents of heat-treated samples did not increase significantly when compared to the control sample. Total phenolic contents were within the range of 0.06 ± 0.05 to 0.08 ± 0.05 mg gallic acid/equivalents g of dry weight. The samples heated at 100°C for 15 and 30 min showed the highest radical scavenging activity at 500 μg/ml with the lowest IC50 values of 10.4 ± 3.11 and 11.67 ± 2.75 μg/ml, respectively. The results suggested that the increased antioxidant activity of P. sajor-caju after the heat treatment might have increased the health beneficial effects to humans.